Short-Term ONX-0914 Administration: Performance and Muscle Phenotype in Mdx Mice - Kwak, Dongmin (Int J Environ Res Public Health, 2020)
Duchenne muscular dystrophy (DMD) is a severe muscle-wasting disease. Although the lack of dystrophin protein is the primary defect responsible for the development of DMD, secondary disease complications such as persistent inflammation contribute greatly to the pathogenesis and the time-dependent progression of muscle destruction. The immunoproteasome is a potential therapeutic target for conditions or diseases mechanistically linked to inflammation. In this study, we explored the possible effects of ONX-0914 administration, an inhibitor specific for the immunoproteasome subunit LMP7 (ß5i), on motor performance, muscular pathology and protein degradation in 7-week old MDX mice, an age when the dystrophic muscles show extensive degeneration and regeneration. ONX-0914 (10 mg/kg) was injected subcutaneously on Day 2, 4, and 6. The mice were evaluated for physical performance (walking speed and strength) on Day 1 and 8. We show that this short-term treatment of ONX-0914 in MDX mice did not alter strength nor walking speed. The physical performance findings were consistent with no change in muscle inflammatory infiltration, percentage of central nuclei and proteasome content. Taken together, muscle structure and function in the young adult MDX mouse model are not altered with ONX-0914 treatment, indicating the administration of ONX-0914 during this critical time period does not exhibit any detrimental effects and may be an effective treatment of secondary complications of muscular dystrophy after further investigations.